A study on the genus Agrilaxia Kerremans, 1903 from Venezuela (Coleoptera: Buprestidae: Buprestinae: Anthaxiini) - Bílý, Svatopluk (Zootaxa, 2015)
Study on the genus Agrilaxia Kerremans, 1903 from Venezuela. Altogether eight species were recorded from this country, four of them are described in this paper: Agrilaxia (Agrilaxia) biformis sp. nov., A. (A.) michaeli sp. nov., A. (A.) stephani sp. nov. and A. (A.) venezuelana sp. nov. All species are illustrated and new species are compared with the most similar/related species. A male of Agrilaxia (A.) balloui Fisher, 1942 is described and the male genitalia are illustrated. New country records are given for Agrilaxia (A.) balloui, A. (A.) costaricensis Obenberger, 1922, A. (A.) glabra Bílý & Brûlé 2013 and A. (A.) simillima Cobos, 1972.